2019
DOI: 10.1038/s42003-018-0248-7
|View full text |Cite
|
Sign up to set email alerts
|

DNA-binding directs the localization of a membrane-integrated receptor of the ToxR family

Abstract: All living cells have a large number of proteins that are anchored with one transmembrane helix in the cytoplasmic membrane. Almost nothing is known about their spatiotemporal organization in whole cells. Here we report on the localization and dynamics of one representative, the pH sensor and transcriptional regulator CadC in Escherichia coli. Fluorophore-tagged CadC was detectable as distinct cluster only when the receptor was activated by external stress, which results in DNA-binding. Clusters immediately di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 51 publications
4
34
0
Order By: Relevance
“…One of the observations arguing against proteolytic cleavage was that external signals can rapidly deactivate the CadC response after the original stimulus, whereas cleavage would irreversibly separate the DNA-binding domain from the signaling input [26]. In contrast, the diffusion and capture mechanism appeared consistent with experiments that imaged fluorophore-labeled CadC in vivo [28]. These experiments showed that localized CadC spots in fluorescent microscopic images form after cells were shifted to a medium that simultaneously provides acid stress and a lysine-rich environment, the two input signals required to stimulate the CadC response [26].…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…One of the observations arguing against proteolytic cleavage was that external signals can rapidly deactivate the CadC response after the original stimulus, whereas cleavage would irreversibly separate the DNA-binding domain from the signaling input [26]. In contrast, the diffusion and capture mechanism appeared consistent with experiments that imaged fluorophore-labeled CadC in vivo [28]. These experiments showed that localized CadC spots in fluorescent microscopic images form after cells were shifted to a medium that simultaneously provides acid stress and a lysine-rich environment, the two input signals required to stimulate the CadC response [26].…”
Section: Introductionmentioning
confidence: 78%
“…A drop in external pH induces dimerization of the periplasmic sensory domain of CadC followed by structural rearrangement of its cytoplasmic linker, permitting the DNA-binding domain of CadC to homodimerize [21,32,35]. The CadC protein number is extremely low (on average 1-3 molecules per cell [28]), mainly due to a low translation rate caused by polyproline stalling, which is only partially relieved by elongation factor P [36].…”
Section: Choice Of Cadc As Experimental Model Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Such co-regulatory mechanisms may not only be widespread for carbohydrate transporters, but also for amino acid transport proteins such as CadC, which is part of an E. coli onecomponent system that receives information on lysine availability from LysP, a lysine-specific membrane-associated amino acid permease ( Figure 2D) (Tetsch and Jung, 2009;Haneburger et al, 2011;Rauschmeier et al, 2014;Brameyer et al, 2019). When lysine is available and the cell is under stress due to low pH, the sensor protein CadC activates the expression of the cadBA genes.…”
Section: Regulatory Influence Of Membrane Transport Proteins and Intrmentioning
confidence: 99%